Konieczność - nieoczywisty wymiar wieczności w koncepcji św. Anzelma z Canterbury - Małecki, Wiesław (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
The main aim of this article is to describe and analyze St. Anselm concept of eternity to present a non-obvious dimension of this idea. Because his philosophical andtheological notion of eternity does not involve only – as common sense suggests – the idea of time but also the very concept of necessity. However, this time, it goes far beyond the understanding of the necessity only in logical terms like it was in case of his ontologicalproof for the existence of God.